Contribution of mir-128 and r3hdm1 in neuronal synaptic maturation /Ching Ai Sze - Ching, Ai Sze (2015)
Synaptogenesis is a crucial process during neuronal development and has to be tightly regulated to ensure the formation of a functional neuronal network. MicroRNAs are increasingly recognised for their role in controlling the expression of genes involved in neuronal development and synaptogenesis. In this study, we aimed to elucidate the role of miR-128 during neuronal development and also to characterise one of its host genes, R3hdm1. Gene expression analysis of miR-128 shows that it is significantly upregulated during neuronal development and correlates with synaptogenesis. In addition, miR-128 is highly abundant in mature neurons. Bioinformatics analysis on miR-128 target genes revealed that most of the miR-128 targets have nucleotide binding properties and are involved in cancer pathways, neurotrophin signalling pathways and focal adhesion. It is known that miR-128 can inhibit another host gene, Arpp21, therefore we sought to investigate if there was a similar interaction between miR-128 and R3hdm1. Our result shows that miR-128 binds to the 5’UTR of R3hdm1 and can suppresse its expression by 19%. We then focused on characterising R3hdm1 further using a combination of techniques including in silico analysis, immunohistochemistry, immunocytochemistry and real-time reverse transcription polymerase chain reaction. Through an in silico method, we determined that the R3HDM1 protein contains a single-stranded nucleic acid binding R3H domain, an RNA-binding SUZ domain, and an additional DNA-binding NUMOD1 domain in humans. Our in silico analysis also indicated that R3HDM1 is not a mitochondrial targeting peptide or a secretory pathway signalling peptide and does not contain any trans-membrane helix. The R3HDM1 protein possesses nuclear localisation and export signals which indicates that the protein can be transported in or out of the nucleus. We first showed that R3hdm1 is ubiquitously expressed in many tissues, but it is most abundant in the adult rat cerebral cortex, followed by liver and heart. Developmentally, R3hdm1 is ubiquitously expressed in the brains of newborn (P0), 14 iv day-old and adult mice (6 - 8 week-old). We found that R3hdm1 mRNA is predominantly localised at the cytoplasmic regions in neurons and is absent in the nucleus. We further investigated expression of R3hdm1 in developing hippocampal neurons, and we found that its expression positively correlates with an increase in synaptogenesis, as measured using a presynaptic marker, Bassoon. Immunocytochemical analysis of hippocampal neurons showed that R3hdm1 appears in punctate form and co-localises with Bassoon, indicating that it is present at the synapse. Furthermore, we found that R3hdm1 mRNA expression is inducible by the Brain-Derived Neurotrophic Factor, especially in mature neurons suggesting that it may be modulated by factors influencing activity-dependent synaptic plasticity. We found that R3hdm1 protein expression level is not affected in miR-128-suppressed neurons or after cognitive training with cross maze escape task. In conclusion, our studies on miR-128 and R3hdm1 have begun to shed new light into the interaction between miR-128 and R3hdm1 and our characterisation of R3hdm1 forms an important platform for further research into this gene as a key synaptic player. Synapse formation and plasticity is a complex mechanism and understanding the role of genes involved in this process is crucial to unlocking new treatments for neurodevelopmental and neurodegenerative disorders.